Detection of LC3‐Associated Phagocytosis (LAP). Issue 1 (21st May 2020) - Martinez, Jennifer
Abstract: Phagocytes, notably macrophages, are critical sentinels of their environment, patrolling for and eradicating unwanted components. The ability of cells to process extracellular cargo in an appropriate manner is important for both clearance of the cargo and eventual return to homeostasis. Although the evolutionarily conserved pathway of autophagy involves the degradation and recycling of unnecessary or dysfunctional cellular components during starvation, we now appreciate that the reach of autophagy extends beyond nutrient deprivation, notably including cellular quality control (e.g., mitophagy) and host defense against internalized pathogens (i.e., xenophagy). Despite being seemingly disparate, autophagic functions are unified as conserved mechanisms for containment and immunosuppression, suggesting an original immune function for autophagy. A recently described pathway called LC3‐associated phagocytosis (LAP) marries the ancient concepts of phagocytosis and autophagy, revealing new ways in which the autophagy machinery, in a molecularly distinct pathway, contributes to the inflammatory response. In this article, protocols to detect LAP by electron microscopy, immunofluorescence, flow cytometry, and phagosome purification are described, allowing the user to detect multiple characteristics of LAP in both qualitative and quantitative manners. Published 2020. U.S. Government. Basic Protocol 1 : Detection of LAP by electron microscopy Basic Protocol 2 : Detection of LAP by confocal microscopy of LC3‐GFP‐expressing cells Alternate Protocol 1 : Detection of LAP by confocal microscopy using immunofluorescence Basic Protocol 3 : Detection of LAP using flow cytometry of LC3‐GFP‐expressing cells Alternate Protocol 2 : Detection of LAP using antibody staining and flow cytometry Basic Protocol 4 : Detection of LAP by western blot of purified LAPosomes